Influence of Hosting Major Sports Events on the Performance of Listed Companies in Host Place - A Discussion of the “Double-edged Sword” Effect of Major Sports Events - Jin Wang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The purpose of this paper is to test the "double-edged sword" effect of hosting major sporting events. This paper took 18 major sports events held in China from 2007 to 2021 as subjects of quasi-natural experiment, and adopted a Propensity Score Matching - Differences in Differences (PSM-DID) method to study the influence of hosting these events on the performance of listed companies in host place based on the panel data of these companies from 2010 to 2021, thereby figuring out the “double-edged sword” effect of hosting major sports events. Our research findings suggest that, hosting major sports events is significantly negatively correlated with the performance of listed companies in host place, and such correlation has passed multiple robustness tests; heterogeneous analysis shows that, hosting major sports events has a negative influence on the performance of state-owned companies and a slight positive influence on the performance of private-owned companies; in terms of companies engaging in different industries, the influence on the performance of listed companies in tourism, real estate, and industry is significantly negative; overall speaking, regardless of international-level or national-level events, hosting such events will pull down the performance of listed companies; in loss-reporting companies, such negative influence on their performance will be amplified, which might worsen their situations further. Therefore, the host place should allocate resources reasonably and effectively and give full play to the role of major sports events in promoting the development of its industries.